Multiplatform Application Technology – Based Heutagogy on Learning Batik: A Curriculum Development Framework - Widiaty, Isma; Riza, Lala Septem; Abdullah, Ade Gafar; Mubaroq, Sugeng Rifqi (Indonesian Journal of Science and Technology, 2020)
This  study  aimed  to  design  a  batik  learning  medium  for vocational high school students in based on multiplatform. The application  made was expected  to support heutagogy approach – based learning and to deal with the development of  science  and  technology  integrated  in  the  curriculum  of vocational high schools. The application developed, namely e-botik,  was  an  integration  of  several  previously-designed applications using Code ignitor (CI) framework. The database used was My-SQL. It is commonly known that Code igniter is an open source web application framework utilized to create dynamic PHP applications. In this study, e-botik consisted of three main  components  including interface, database,  and application  programming  interface  (API).  Some  of  the applications combined were ARtikon_joyful (Android-based), Video Kasumedangan Batik (movie player), Nalungtik  Batik (desktop-based),  Digi_Learnik  (web-based),  Batik  UPI (manual),  Batik  Cireundeu  (manual),  and  Lembar  Balik (manual). The combination proceeded web-based so that it was  compatible  with  various  operating  systems.  The application (e-botik) was designed and then tested. The test was  performed  through  whitebox  testing  and  blackbox testing. The results of the test showed that it ran well and was able to be used a batik learning media. It is expected that students  can  utilize  e-botik  in  selecting  topics  of  learning batik in accordance with their competences and needs. This condition enables e-botik to support learning batik through heutagogical approach. In addition, the application was also validated in terms of both system and usage aspects.